PENGARUH PUPUK TRICHODERMA SP. DENGAN MEDIA TUMBUH BERBEDA TERHADAP PERTUMBUHAN VEGETATIF TANAMAN CABAI MERAH BESAR (Capsicum Frutescens L.) - I Wayan Suanda (JURNAL WIDYA BIOLOGI, 2019)
This research aimed to find out the effects of Trichoderma sp. fertilizers with different growing media on the vegetative growth of chili plants and to find out the best growing media to make it grow optimally.This research was conducted in the Biologi Laboratory at FPMIPA IKIP PGRI Bali from April to June, 2018. The research was done in several growing media; treatmen P0 (without the Trichoderma sp. fertilizer), P1 (Trichoderma sp. fertilizer from taro media), P2 (Trichoderma sp. fertilizer from cassava media), P3 (Trichoderma sp. fertilizer from sweet potato media), P4 (Trichoderma sp. fertilizer from corn media), P5 (Trichoderma sp. fertilizer from potato media). These treatments were repeated four times each. The population in this study were all chili pepper seeds of F1 Megatop variety with a total of 100 plants and a sample of 72 plant that were three weeks old. Each group contained of three chili plants. The data collected in this study were about the height and number of leaves on the chili plants. The data were analyzed using the analysis o variance (ANOVA) with F test and a 5% significance level followed by the LSD test.Based on the analysis, there are several effects of Trichoderma sp. fertilizer with different growing media on the vegetative growth of chili plants. The results showed that treatment P4 (Trichoderma sp. fertilizer from corn media) have the most effective and optimal effects on the chili plants.